PEMERINGKATAN RISIKO KEAMANAN SISTEM JARINGAN KOMPUTER POLITEKNIK KOTA MALANG MENGGUNAKAN CVSS DAN FMEA - Betta Wahyu Retna Mulya; Avinanta Tarigan (ILKOM Jurnal Ilmiah, 2018)
The vulnerability of a computer network system is a weakness, lack or hole in the system, which can be exploited by attackers to carry out an attack that may endanger the confidentiality, integrity or availability of a system. The filling process requires a security vulnerability analysis according to the severity to determine the priority scales of handling. The analysis used in determining priority scales of handling is the combination of CVSS and FMEA-based analysis method. The analysis result from both methods shows that the numbers of risk priority and vulnerability become a benchmark in risk prioritizing and mitigation the risk to Politeknik Kota Malang party, with the priority order: ‘Singa’, ‘Sierra’, ‘Dino’, and ‘Leopard’. The priority scales show that the vulnerability levels, that must be handled, have number range between 40% up to 60%. The combination of CVSS and FMEA methods can determine the handling level based on the potential impacts caused by the vulnerability in computer network system of Politeknik Kota Malang.